The Analysis of Korean Clinical Studies on the Effect of Pharmacopuncture for Whiplash Injury after Traffic Accidents - Jung Min Yun; Na Yeon Hur; Kyeong Han Kim (Korean Pharmacopuncture Institute, 2020)
Objectives: Whiplash injury is one of the major diseases in recent times because of in-creasing traffic accidents. This review aims to analyze the overall trend of studies on phar-macopuncture for whiplash injury after traffic accidents.Methods: We searched through 4 Korean electronic databases from 2001 up to October 2020 for relevant clinical studies for whiplash injury after traffic accidents, regardless of the patients' age, gender, or race. We included studies that had an intervention group re-ceiving pharmacopuncture therapy with or without other additional treatments, and also included studies that had a control group receiving sham treatment or active treatment such as physical therapy and herbal medication. For the clinical outcomes, we did not place any restrictions on evaluation scales if they are objective metrics.Results: We included 6 randomized controlled trials (RCTs) and 10 non-randomized con-trolled trials (nRCTs). 10 nRCTs were divided into 4 categories that were case-control stud-ies, case series, case report, and retrospective observational study. In RCTs, Hwangryun-haedoktang (黃蓮解毒湯) pharmacopuncture was the most frequently used. In nRCTs, Jungsong-ouhyul (中性瘀血) pharmacopuncture, and bee venom pharmacopuncture were the most frequently used. As target points of Hwangryun-haedoktang pharmacopuncture, Ashi-points, Jianjing (GB21), and Fengchi (GB20) were the most frequently used. As target points of Jungsong-ouhyul pharmacopuncture, Ashi-points were the most frequently used. And as target points of Bee venom pharmacopuncture, Fengchi (GB20) was the most fre-quently used. Conclusion: Hwangryun-haedoktang pharmacopuncture, bee venom pharmacopuncture, and Jungsong-ouhyul pharmacopuncture were mainly used for whiplash injury, and their usual target points were Jianjing (GB21), Fengchi (GB20), and Ashi-points. However, a high level of evidence should be conducted through studies with systematic methodology in the future.